High-intensity interval training on unstable vs stable surfaces: effects on explosive strength, balance, agility, and Tsukahara vault performance in gymnastics - Khaled Abuwarda; Mostafa Mansy; Mohamed Megahed (Pedagogy of Physical Culture and Sports, 2024)
Background and Study Aim. This study compares the effects of high-intensity interval training (HIIT) on unstable and stable surfaces on explosive strength, balance, agility, and Tsukahara vault performance in gymnastics.